The Marketing Mix, Customers' Attitude, and Purchasing Intention in Social Commerce with Internet Access as a Moderating Variable - Randrianantenaina Solohery Mampionona Aime; Gancar Candra Premananto; Sedera Rakotoarisoa (Universitas Airlangga, 2022)
Objective: Based on cognitive-affective-conative theory, this study aims to create an integrated model that investigates the effects of six marketing-mix components (cognitive) on purchase intention (cognitive) in social commerce (SC) via customer's attitude toward SC (affective). Design/Methods/Approach: An online survey was used to facilitate the collecting data procedure. A structural equation model with partial least squares is employed to analyze valid data from 200 members of the SC store (Coulisses) who have never purchased in SC. Findings The results from PLS analysis show that only two components of the SC marketing mix (SCMM) have significant effects on customers' attitude toward social commerce (Att.), which is social influence (SI) and SC needs (SCN). Moreover, customers' attitude toward SC value positively influences purchase intention (PI). Another finding from this research was that internet access (IA) could not moderate the relationship between Att. and PI. Originality: This paper explained the overarching impacts of SCMM components on PI in SC, as mediated by Att. This study enriches the SCMM theory, which is scarcely discussed nowadays despite the rapid development of SC. Practical/Policy implication: Practical implications are made for new and old online sellers who want to expand their channels. Sellers need to focus on the role of influencers in their trading business. Moreover, sellers should accommodate more product varieties at competitive prices and quality to compete with offline shops' products.